Preparation method and application of cerium-based metal-organic framework composite catalytic material

CN122912918APending Publication Date: 2026-10-16SOUTHWEAT UNIV OF SCI & TECH +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610995078.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-06
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

二氧化碳固有的化学惰性要求传统氢化反应需在极端条件(高温高压)下进行,而且依赖H2作为氢源带来了显著成本障碍,阻碍其工业应用

Benefits of technology

[0015] This invention provides at least the following beneficial effects: It offers a cerium-based metal-organic framework composite catalytic material, CeHfZr-UiO-66, which adsorbs water to form a surface hydrogen bond network and utilizes high-energy electrons to generate solvated hydrogen radicals and hydroxyl radicals in situ, thereby effectively promoting the conversion of CO2 to C2H4. In a simulated atmosphere containing approximately 20% CO2, CeHfZr-UiO-66 achieved a C2H4 yield of 164.6 μmol/(g·h), nearly 15 times higher than Ce-UiO-66, and remained stable for 180 minutes. This invention provides a feasible material design strategy for the non-thermal plasma-driven conversion of CO2 to C2H4.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912918A_ABST
    Figure CN122912918A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a cerium-based metal organic framework composite catalytic material, which comprises the following steps: uniformly mixing terephthalic acid, hydrochloric acid and N,N-dimethylformamide, adding metal chloride, stirring to obtain a mixed solution; transferring the mixed solution into a reaction kettle, heating and reacting, collecting and washing precipitates, and vacuum drying to obtain the cerium-based metal organic framework composite catalytic material. The application provides a cerium-based metal organic framework composite catalytic material CeHfZr-UiO-66 and a preparation method thereof. The catalytic material can adsorb water to form a surface hydrogen bond network, and in-situ generate solvated hydrogen radicals and hydroxyl radicals by using high-energy electrons, so as to effectively promote the conversion of CO2 into C2H4, and provide a feasible material design strategy for the conversion of CO2 into C2H4 under the non-thermal plasma driving.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst preparation technology, and more specifically, this invention relates to a method for preparing and applying a cerium-based metal-organic framework composite catalytic material. Background Technology

[0002] Fossil fuel extraction has driven societal development; however, excessive carbon dioxide emissions have exacerbated global warming and severe environmental problems. Mitigating these impacts requires reducing atmospheric carbon dioxide concentrations, which can be achieved through carbon sequestration or its conversion into high-value chemicals. As an abundant and readily available carbon feedstock, carbon dioxide can be converted into high-value products through carbon dioxide reduction (CO2RR) technology, thereby achieving an artificial carbon cycle and bringing environmental and economic benefits while reducing dependence on fossil fuels. The inherent chemical inertness of carbon dioxide requires traditional hydrogenation reactions to be carried out under extreme conditions (high temperature and high pressure), and the reliance on H2 as a hydrogen source presents a significant cost barrier, hindering its industrial application. Therefore, developing efficient processes to directly reduce carbon dioxide into high-value carbon-based products is crucial.

[0003] As a cornerstone of the petrochemical industry, ethylene (C2H4) is a crucial strategic target for achieving carbon cycle through the catalytic conversion of carbon dioxide. Many industrial processes generate waste gases containing both carbon dioxide and water vapor, making their direct co-conversion into high-value ethylene products particularly attractive in practical applications. Non-thermal plasma (NTP) technology has emerged as a promising approach for the direct decomposition of carbon dioxide. Specifically, high-energy electrons generated during the discharge process efficiently transfer energy to carbon dioxide molecules through collisions, enabling convenient excitation and subsequent degradation at room temperature. NTP technology can achieve the direct co-conversion of carbon dioxide and water, while the introduction of a catalyst significantly affects the conversion efficiency. However, utilizing water as a hydrogen source for the direct conversion of carbon dioxide to ethylene via NTP remains challenging. The strong discharge characteristics and unique energy transfer mode of the NTP system can dissociate water vapor into gaseous hydrogen radicals (·H) and hydroxyl radicals (·OH). As key intermediates, ·H radicals participate in various hydrogenation reaction pathways to generate different carbon products, thus affecting the selectivity for the target product. It is noteworthy that ·H radicals are key species inducing and promoting C / C bond coupling during ethylene synthesis, transforming into *H radicals that directly participate in the reaction after adsorption on the surface. Simultaneously, ·H radicals can also be consumed by participating in the formation of C / C bonds and the molecular skeleton, contributing to the construction of other carbon products (such as C2H6O and C3H6O). Furthermore, free gaseous ·OH radicals within the plasma chamber may initiate non-selective oxidation reactions, damaging the catalyst's bulk structure and shortening its lifetime, thereby reducing catalytic activity. Therefore, optimizing the morphological distribution and functional state of ·H and ·OH radicals on the catalyst surface is an effective strategy for improving the catalytic activity and ethylene selectivity of the NTP system. Summary of the Invention

[0004] One object of the present invention is to solve at least the above-mentioned problems and / or defects, and to provide at least the advantages described below.

[0005] To achieve these objectives and other advantages of the present invention, a method for preparing a cerium-based metal-organic framework composite catalytic material is provided, comprising the following steps: Step 1: Mix terephthalic acid, hydrochloric acid and N,N-dimethylformamide (DMF) thoroughly, add metal chloride, and stir to obtain a mixed solution; Step 2: Transfer the mixed solution to a reaction vessel, heat the reaction, collect the precipitate and wash it, then vacuum dry it to obtain the cerium-based metal-organic framework composite catalytic material.

[0006] Preferably, in step one, the molar volume ratio of terephthalic acid, hydrochloric acid and N,N-dimethylformamide is 3~5 mmol:0.2~0.6 mL:10~20 mL; and the concentration of hydrochloric acid is 36~38 wt%.

[0007] Preferably, in step one, the metal chloride includes one or more of cerium chloride, hafnium chloride, and zirconium chloride.

[0008] Preferably, in step one, the metal chloride is a combination of cerium chloride, hafnium chloride, and zirconium chloride.

[0009] Preferably, in step one, the molar ratio of cerium chloride, hafnium chloride, and zirconium chloride is 1~2:1~2:1~2.

[0010] Preferably, in step one, the molar ratio of terephthalic acid to metal chloride is 1:1 to 3.

[0011] Preferably, in step two, the heating reaction temperature is 110~130℃ and the time is 12~36h.

[0012] Preferably, in step two, the washing process involves sequentially washing with N,N-dimethylformamide and methanol 2 to 5 times.

[0013] Preferably, in step two, the vacuum drying temperature is 50~70℃ and the time is 8~20h.

[0014] Application of a cerium-based metal-organic framework composite catalytic material prepared by the method described above in radiation-catalyzed CO2 conversion.

[0015] This invention provides at least the following beneficial effects: It offers a cerium-based metal-organic framework composite catalytic material, CeHfZr-UiO-66, which adsorbs water to form a surface hydrogen bond network and utilizes high-energy electrons to generate solvated hydrogen radicals and hydroxyl radicals in situ, thereby effectively promoting the conversion of CO2 to C2H4. In a simulated atmosphere containing approximately 20% CO2, CeHfZr-UiO-66 achieved a C2H4 yield of 164.6 μmol / (g·h), nearly 15 times higher than Ce-UiO-66, and remained stable for 180 minutes. This invention provides a feasible material design strategy for the non-thermal plasma-driven conversion of CO2 to C2H4.

[0016] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Attached Figure Description

[0017] Figure 1 a is a schematic diagram of the synthesis process of CeHfZr-UiO-66; Figure 1 b is the SEM image of CeHfZr-UiO-66; Figure 1 c is an HRTEM image of CeHfZr-UiO-66; Figure 1 d represents the thermogravimetric analysis curves of Ce-UiO-66 and CeHfZr-UiO-66; Figure 1 e represents the FTIR spectra of Ce-UiO-66, CeHf-UiO-66, CeZr-UiO-66, and CeHfZr-UiO-66; Figure 1 f represents the XRD patterns of Ce-UiO-66, CeHf-UiO-66, CeZr-UiO-66, and CeHfZr-UiO-66; Figure 1 g represents the ESR spectra of Ce-UiO-66, CeHf-UiO-66, CeZr-UiO-66, and CeHfZr-UiO-66; Figure 2 SEM images of (a) Ce-UiO-66, (b) CeHf-UiO-66, (c) CeZr-UiO-66, and (d) CeHfZr-UiO-66; Figure 3 Carbon dioxide adsorption curves for Ce-UiO-66, CeHf-UiO-66, CeZr-UiO-66 and CeHfZr-UiO-66; Figure 4 a represents the thermogravimetric analysis results of CeHfZr-UiO-66 before and after water adsorption; Figure 4 b shows the FTIR spectra of Ce-UiO-66, CeHf-UiO-66, CeZr-UiO-66, and CeHfZr-UiO-66 after water adsorption; Figure 4 c represents the solid-state NMR spectra of Ce-UiO-66 and CeHfZr-UiO-66 before and after water adsorption; Figure 4 d represents the XPS spectra of CeHfZr-UiO-66 before and after water adsorption; Figure 4 e represents the Hf 4f XPS spectra of CeHfZr-UiO-66 before and after water adsorption; Figure 4 f represents the Zr 3d XPS spectra of CeHfZr-UiO-66 before and after water adsorption; Figure 4 g and Figure 4 h is the in-situ FTIR spectrum of CeHfZr-UiO-66 during the water adsorption process; Figure 5 The carbon dioxide conversion rate of CeHfZr-UiO-66 under different plasma power and gas flow rate (pure carbon dioxide); Figure 6 The relationship between carbon dioxide conversion and carbon monoxide selectivity of CeHfZr-UiO-66 and carbon dioxide concentration. Figure 7 The results represent the long-term operational stability of CeHfZr-UiO-66; Figure 8 Analysis of carbon dioxide conversion rate and catalytic products of CeHfZr-UiO-66 under reactant gases with different water contents; Figure 9 Product selectivity of CeHfZr-UiO-66 under reaction gases with different water contents; Figure 10 The carbon dioxide conversion rate and ethylene yield of Ce-UiO-66 and CeHfZr-UiO-66 under aqueous and anhydrous conditions; Figure 11 a represents the Raman spectra of Ce-UiO-66 and CeHfZr-UiO-66 before and after catalysis; Figure 11 b represents the thermogravimetric analysis results of Ce-UiO-66 and CeHfZr-UiO-66 after catalysis; Figure 11 c represents the OES spectra of Ce-UiO-66 and CeHfZr-UiO-66 during the catalytic process; Figure 11 d represents the EIS spectra of Ce-UiO-66 and CeHfZr-UiO-66; Figure 11 e represents the UPS spectra of Ce-UiO-66 and CeHfZr-UiO-66; Figure 11 f represents the plasma discharge waveforms of Ce-UiO-66 and CeHfZr-UiO-66; Figure 11 g represents the LSV spectra of Ce-UiO-66 and CeHfZr-UiO-66; Figure 11 h represents the EPR spectra of Ce-UiO-66 and CeHfZr-UiO-66; Figure 11 i represents the FTIR spectra of Ce-UiO-66 and CeHfZr-UiO-66 after catalysis; Figure 12 A schematic diagram of the NTP-catalyzed hydrogenation mechanism of carbon dioxide on the CeHfZr-UiO-66 surface. Detailed Implementation

[0018] The present invention will now be described in further detail with reference to the accompanying drawings, so that those skilled in the art can implement it based on the description.

[0019] It should be understood that terms such as “having,” “comprising,” and “including” as used herein do not exclude the presence or addition of one or more other elements or combinations thereof.

[0020] Example 1 A method for preparing a cerium-based metal-organic framework composite catalytic material includes the following steps: Step 1: Mix 4 mmol terephthalic acid, 0.4 mL 37 wt% hydrochloric acid and 15 mL N,N-dimethylformamide, and stir magnetically for 10 minutes to ensure complete dissolution and uniform dispersion. Then add 4 mmol CeCl3·7H2O and continue stirring for 30 minutes to obtain a mixed solution. Step 2: Transfer the mixed solution to a stainless steel high-pressure reactor lined with polytetrafluoroethylene and react at 120°C for 24 hours. After natural cooling to room temperature, collect the precipitate by centrifugation and wash it three times with DMF and methanol respectively. During each washing, perform ultrasonic treatment for 5 minutes to remove unreacted ligands and soluble byproducts. Dry the obtained solid under vacuum at 60°C for 12 hours to obtain the cerium-based metal-organic framework composite catalytic material, denoted as Ce-UiO-66.

[0021] Example 2 A method for preparing a cerium-based metal-organic framework composite catalytic material includes the following steps: Step 1: Mix 4 mmol terephthalic acid, 0.4 mL 37 wt% hydrochloric acid and 15 mL N,N-dimethylformamide, and stir magnetically for 10 minutes to ensure complete dissolution and uniform dispersion. Then add 4 mmol CeCl3·7H2O and 4 mmol HfCl4, and continue stirring for 30 minutes to obtain a mixed solution. Step 2: Transfer the mixed solution to a stainless steel high-pressure reactor lined with polytetrafluoroethylene and react at 120°C for 24 hours. After natural cooling to room temperature, collect the precipitate by centrifugation and wash it three times with DMF and methanol respectively. During each washing, perform ultrasonic treatment for 5 minutes to remove unreacted ligands and soluble byproducts. Dry the obtained solid under vacuum at 60°C for 12 hours to obtain the cerium-based metal-organic framework composite catalytic material, denoted as CeHf-UiO-66.

[0022] Example 3 A method for preparing a cerium-based metal-organic framework composite catalytic material includes the following steps: Step 1: Mix 4 mmol terephthalic acid, 0.4 mL 37 wt% hydrochloric acid and 15 mL N,N-dimethylformamide, and stir magnetically for 10 minutes to ensure complete dissolution and uniform dispersion. Then add 4 mmol CeCl3·7H2O and 4 mmol ZrCl4, and continue stirring for 30 minutes to obtain a mixed solution. Step 2: Transfer the mixed solution to a stainless steel high-pressure reactor lined with polytetrafluoroethylene and react at 120°C for 24 hours. After natural cooling to room temperature, collect the precipitate by centrifugation and wash it three times with DMF and methanol respectively. During each washing, perform ultrasonic treatment for 5 minutes to remove unreacted ligands and soluble byproducts. Dry the obtained solid under vacuum at 60°C for 12 hours to obtain the cerium-based metal-organic framework composite catalytic material, denoted as CeZr-UiO-66.

[0023] Example 4 A method for preparing a cerium-based metal-organic framework composite catalytic material includes the following steps: Step 1: Mix 4 mmol terephthalic acid, 0.4 mL 37 wt% hydrochloric acid and 15 mL N,N-dimethylformamide, and stir magnetically for 10 minutes to ensure complete dissolution and uniform dispersion. Then add 4 mmol CeCl3·7H2O, 4 mmol HfCl4 and 4 mmol ZrCl4, and continue stirring for 30 minutes to obtain a mixed solution. Step 2: Transfer the mixed solution to a stainless steel high-pressure reactor lined with polytetrafluoroethylene and react at 120°C for 24 hours. After natural cooling to room temperature, collect the precipitate by centrifugation and wash it three times with DMF and methanol respectively. During each washing, perform ultrasonic treatment for 5 minutes to remove unreacted ligands and soluble byproducts. Dry the obtained solid under vacuum at 60°C for 12 hours to obtain the cerium-based metal-organic framework composite catalytic material, denoted as CeHfZr-UiO-66.

[0024] To further improve the CO2 conversion rate and C2H4 yield, this invention post-processes the cerium-based metal-organic framework composite catalytic material obtained in step two. CeHfZr-UiO-66 is coated and modified with thiol-functionalized Ce-UiO-66 to obtain a more stable cerium-based metal-organic framework composite catalytic material CeHfZr-UiO-66 / Ce-SH with more active sites. This further enhances the adsorption and activation of CO2 by the catalytic material and promotes the generation of C2H4. The introduction of thiol groups can regulate the electronic structure of the catalytic material, enhance the adsorption and activation of CO2, and improve the hydrophilicity of the material surface. Synergistically with CeHfZr-UiO-66, it promotes the production of C2H4 from the CO2 / H2O system. Microwave heating effectively improves reaction efficiency, shortens reaction time, improves product morphology and structural stability, increases specific surface area, and enhances the ability to capture CO2.

[0025] The specific post-processing method includes the following steps: S1. Mix 3-5 mmol of 2,5-dimercaptoterephthalic acid, 3-5 mmol of cerium chloride, 6-20 mL of acetic acid and 20-80 mL of N,N-dimethylformamide evenly, add 0.5-2 g of the cerium-based metal-organic framework composite catalyst obtained in step 2, and stir to obtain a mixed solution; S2. Transfer the mixed solution to a microwave reactor, microwave heat it to 110~130℃ for 0.5~2h, collect the precipitate and wash it, then vacuum dry it at 50~70℃ for 8~20h to obtain the post-treated cerium-based metal-organic framework composite catalytic material.

[0026] Example 5 The cerium-based metal-organic framework composite catalytic material (CeHfZr-UiO-66) obtained in Example 4 underwent post-processing, including the following steps: S1. Mix 4 mmol of 2,5-dimercaptoterephthalic acid, 4 mmol of CeCl3·7H2O, 12 mL of acetic acid and 50 mL of N,N-dimethylformamide, and stir magnetically for 10 minutes to ensure complete dissolution and uniform dispersion. Then add 1 g of CeHfZr-UiO-66 prepared in Example 4 and continue stirring for 30 minutes to obtain a mixed solution. S2. The mixed solution was transferred to a polytetrafluoroethylene-lined microwave reactor and microwave-heated to 120°C for 1 hour. After natural cooling to room temperature, the precipitate was collected by centrifugation and washed three times with DMF and methanol, respectively. During each washing, the precipitate was sonicated for 5 minutes to remove unreacted ligands and soluble byproducts. The resulting solid was vacuum-dried at 60°C for 12 hours to obtain the post-treated cerium-based metal-organic framework composite catalytic material, denoted as CeHfZr-UiO-66 / Ce-SH.

[0027] Example 6 In this embodiment, ZrCl4 was used to replace CeCl3·7H2O, and the remaining steps were the same as in Example 5, to obtain the post-treated cerium-based metal-organic framework composite catalytic material, denoted as CeHfZr-UiO-66 / Zr-SH.

[0028] Example 7 In this embodiment, terephthalic acid was used to replace 2,5-dimercaptoterephthalic acid, and the remaining steps were the same as in Example 5, to obtain the post-treated cerium-based metal-organic framework composite catalytic material, denoted as CeHfZr-UiO-66 / Ce.

[0029] Example 8 In this embodiment, 2,5-diaminoterephthalic acid was used to replace 2,5-dimercaptoterephthalic acid, and the remaining steps were the same as in Example 5, to obtain the post-treated cerium-based metal-organic framework composite catalytic material, denoted as CeHfZr-UiO-66 / Ce-NH.

[0030] Example 9 In this embodiment, microwave heating is not used in step S2. The mixed solution is transferred to a stainless steel high-pressure reactor lined with polytetrafluoroethylene and reacted at 120°C for 24 hours. The remaining steps are the same as in Example 5, and the post-treated cerium-based metal-organic framework composite catalytic material is obtained, denoted as CeHfZr-UiO-66 / Ce-SH-24.

[0031] Figure 1 a represents the solvothermal synthesis process of a cerium-based metal-organic framework composite catalyst (CeHfZr-UiO-66), in which the amount of doped metal is controlled by adjusting the metal ion supply. Scanning electron microscopy (SEM) analysis revealed the influence of elemental composition and doping amount on the catalyst morphology. Figure 1 b and Figure 2 The influence of variations in metal element type and doping level on nanoparticle shape is negligible, attributed to the increased structural entropy enhancing the framework's tolerance to ion doping. The irregular stacking of these nanoparticles effectively increases mesoporous porosity, promoting carbon dioxide mass transfer during catalysis and thus improving catalytic efficiency. The mesoporous structure of CeHfZr-UiO-66 was further confirmed by N2-BET analysis, with a pore size of approximately 14 nm. Transmission electron microscopy (TEM) and corresponding energy dispersive spectroscopy images clearly demonstrate the spatial distribution of Ce, Hf, Zr, and O elements in this material, confirming successful metal ion doping. Figure 1 c). For example Figure 1 As shown in Figure d, thermogravimetric analysis (TG) revealed weight loss peaks in both CeHfZr-UiO-66 and Ce-UiO-66 within the 400–600 °C range, attributed to the disintegration of the UiO-66 framework. The organic framework decomposition temperature of CeHfZr-UiO-66 was significantly lower than that of Ce-UiO-66, which is closely related to the polarization effect of the active centers formed by multi-metal doping on the coordinated carboxyl groups at the nodes.

[0032] To determine the active sites for carbon dioxide catalysis in CeHfZr-UiO-66, we investigated the distribution of metal ions within the UiO-66 framework. Fourier transform infrared (FTIR) spectroscopy provided structural and coordination information. Figure 1 As shown in Figure e, the samples from Examples 1-4 were stored at 1300-1800 cm⁻¹. -1Absorption peaks corresponding to carboxylic acid groups, benzene rings, and carbonyl groups appeared within the range, indicating that elemental doping did not disrupt the organic framework structure. Furthermore, absorption peaks were observed at ~551 cm⁻¹. -1 The observed peaks are attributed to the M-μ3-O vibrations resulting from the coordination of metal ions with the μ3-O bonds in terephthalic acid. The M-μ3-O vibration peak intensity in the CeHfZr-UiO-66 sample is significantly weaker than that in other samples, indicating that more metal ions remain uncoordinated with oxygen-containing groups within the framework. X-ray diffraction (XRD) further clarifies the coordination of metal ions within the framework: such as... Figure 1 As shown in f, the XRD patterns all exhibit typical UiO-66 crystal phase characteristics. The observed leftward shift of the peak positions indicates that the lattice expanded with the gradual incorporation of metal ions. This change provides evidence for the formation of metal clusters at the node connections after metal ions are inserted into the UiO-66 structure. Electron spin resonance (ESR) spectroscopy analysis of CeHfZr-UiO-66 shows a significant signal at g = 2.002, which is attributed to unsaturated Lewis acid sites formed within the framework of uncoupled metal centers. Figure 1 g). These Lewis acid sites can polarize C=O bonds during carbon dioxide catalysis, becoming core sites for carbon dioxide binding and activation. Furthermore, the carbon dioxide adsorption isotherm shows that CeHfZr-UiO-66 in Example 4 exhibits significantly higher carbon dioxide capture capacity compared to Examples 1-3. Figure 3 In summary, these results confirm that the metal cluster successfully intercalates into the nodal sites of the UiO-66 framework and acts as a strong Lewis acid active site to promote the catalytic conversion of carbon dioxide.

[0033] Since water is the only hydrogen source in nonthermal plasma (NTP) catalysis, studying its adsorption behavior on the catalyst surface is crucial for understanding the carbon dioxide conversion mechanism. To investigate the speciation of water on the catalyst surface, we monitored the changes in the catalyst surface and interface before and after water adsorption. Thermogravimetric analysis (TGA) curves of CeHfZr-UiO-66 material after water adsorption showed a significant dehydration weight loss peak below 120 °C, a characteristic attributed to its abundant active sites (…). Figure 4 a). Meanwhile, the reduced weight loss due to framework collapse and the enhanced DTG peak after water adsorption indicate that water inhibited the catalytic degradation of ligands by strong Lewis acid sites, maintaining the integrity of the framework structure before synchronous collapse at the critical point. Figure 4 As shown in b, after the same water adsorption treatment, Examples 1-3 were at 3000-3600 cm⁻¹ -1 The significantly decreased intensity of the -OH peak in the region indicates that CeHfZr-UiO-66 adsorbed more water to promote carbon dioxide conversion. Solid-state ¹H NMR spectroscopy further elucidated the distribution of water species on the surface of the catalytic material. Figure 4c shows that both CeHfZr-UiO-66 and Ce-UiO-66 exhibit significant hydrochemical shifts at approximately 3 ppm after water adsorption. The ¹H signal of CeHfZr-UiO-66 shifts significantly towards the lower field, attributed to the strong deshielding effect generated by proton participation in the surface hydrogen bond network. X-ray photoelectron spectroscopy (XPS) was used to analyze the chemical states of surface elements and probe water adsorption at specific sites. The scanning spectra indicate that increased metal doping promotes the formation of competitive clusters, thereby reducing the proportion of the corresponding elements. The cerium content on the CeHfZr-UiO-66 surface decreases significantly after water adsorption, confirming that cerium is the main water adsorption site (…). Figure 4 d). High-resolution XPS spectra showed that the proportion of low-valence hafnium on the CeHfZr-UiO-66 surface increased significantly after water adsorption (from 42.6% to 54.6%), while the 3d binding energy of zirconium showed a negative shift. Figure 4 (e and 4f). These results further indicate that the hafnium and zirconium sites on the CeHfZr-UiO-66 surface promote water adsorption through hydrogen bonding.

[0034] In-situ FTIR spectroscopy was used to track the dynamic adsorption process of water on the CeHfZr-UiO-66 surface. Figure 4 As shown in g, after water vapor is introduced into the sealed chamber, it reaches a temperature of ~3430cm. -1 (OH stretching vibration) and ~1620cm -1 The presence of a characteristic peak at the (HOH bending vibration) indicates that water is effectively captured. With prolonged exposure, the accumulated water forms an interconnected network through strong hydrogen bonds, leading to peak broadening and a low-frequency shift. Figure 4 In summary, these results demonstrate that CeHfZr-UiO-66 constructs a hydrogen-bonded network microenvironment through water adsorption, providing an abundant hydrogen source for the catalytic conversion of carbon dioxide.

[0035] Non-thermal plasma (NTP) catalytic experiment: The core structure of the coaxial dielectric barrier discharge (DBD) reactor used in this invention is a double-layer quartz tube: aluminum foil is wrapped around the outer wall of the quartz tube (outer diameter 11 mm, inner diameter 8 mm) as a grounding electrode, and connected to the grounding terminal of the plasma power supply; another quartz tube (outer diameter 6 mm, inner diameter 4 mm) is placed along the reactor axis, and a 4 mm diameter stainless steel rod is inserted inside as a high-voltage electrode. The effective length of the plasma discharge zone is 50 mm, and the discharge gap width is 1 mm. 0.2 g of catalytic material is uniformly filled into the discharge gap, and both ends are fixed with quartz wool. The reactor is connected to a CTP-2000K low-temperature plasma experimental power supply. Reaction gas is introduced into the reactor for 10 minutes to replace the air in the system and check for leaks to ensure that the device is well sealed. Then the power supply is turned on and the power is adjusted to start the reaction. The working frequency is set to 400 Hz, and the input power is adjusted from 10 to 25 W by adjusting the applied voltage.

[0036] Using pure carbon dioxide as the reactant gas, the catalytic parameters were first optimized by adjusting the input power (10~25W) and gas flow rate (10~30sccm). Under conditions of 15W power and 20sccm flow rate, the carbon dioxide conversion rate of CeHfZr-UiO-66 reached 11.1%, which is 3.7 times higher than the worst-case conversion rate (2.96%). Figure 5 Deviations from these parameters lead to a decrease in conversion, attributed to insufficient carbon dioxide reaction and catalyst structural degradation. The suitability of the catalyst can be assessed by varying the carbon dioxide concentration: such as... Figure 6 As shown in Table 1, when the carbon dioxide concentration was 20% (the remainder being argon), the conversion rate of CeHfZr-UiO-66 increased to 22.8%, higher than Ce-UiO-66, CeHf-UiO-66, and CeZr-UiO-66, demonstrating its application potential in industrial waste gas treatment. Although the conversion rate reached 58.53% under 2% carbon dioxide conditions, the carbon monoxide selectivity decreased to 44.96% due to excessive carbon dioxide cracking and carbon deposition. Unless otherwise stated, all subsequent experiments used optimized parameters (15W, 20sccm, and 20% CO2). Long-term stability tests showed that CeHfZr-UiO-66 maintained approximately 26% carbon dioxide conversion and nearly 100% carbon monoxide selectivity after 180 minutes of continuous operation, demonstrating excellent durability. Figure 7 These results demonstrate that CeHfZr-UiO-66 exhibits superior carbon dioxide catalytic activity under anhydrous conditions, and the generated carbon monoxide can be further converted into adsorbed carbon monoxide (*CO), which is a key intermediate in the CC coupling reaction.

[0037] Table 1 H2O is the sole hydrogen source for carbon dioxide catalysis in the NTP system. Before entering the reactor, the CO2 reaction gas is humidified using a pure water bubbler to introduce water vapor. The concentration of water vapor is controlled by temperature (room temperature (20℃), 40℃, 60℃), directly affecting product selectivity. After the introduction of water, the selectivity of CeHfZr-UiO-66 for carbon monoxide is significantly reduced, and ethylene (6.47%) is detected as the only high-carbon product (C2H6O or C3H6O is not detected). Figure 8 This result directly indicates that carbon monoxide undergoes a deoxygenation reaction with adsorbed hydrogen (*H) and a CC coupling reaction to produce ethylene. Furthermore, increasing the water content gradually increases the yields of methane (CH4) and ethane (C2H6), further demonstrating that increased hydrogen supply promotes the activation of methane and its participation in the CC coupling reaction to produce ethane. Figure 9 ).like Figure 10 As shown in Table 2, CeHfZr-UiO-66 achieved an ethylene yield of 164.6 μmol / (g·h) at room temperature, significantly higher than Ce-UiO-66, CeHf-UiO-66, and CeZr-UiO-66. In summary, compared to Examples 1-3, the CeHfZr-UiO-66 prepared in Example 4 effectively adsorbs and activates carbon dioxide while converting water vapor into hydrogen, thereby promoting the CC coupling reaction in the ethylene synthesis process.

[0038] Table 2 The superior carbon dioxide conversion performance of CeHfZr-UiO-66 prompted us to explore the synthetic route of ethylene. In the NTP system, high-energy electrons lower the reaction barrier for carbon dioxide, but also indiscriminately bombard the catalyst, potentially altering its surface structure. For example... Figure 11 As shown in Figure a, the Raman peaks of CeHfZr-UiO-66 remained intact after the reaction. This is attributed to the hydrogen bond network formed by the absorption of high-energy electrons by surface-adsorbed water molecules, thus maintaining its structural integrity. Notably, the thermogravimetric curve of Ce-UiO-66 after use showed a carbon weight loss peak at approximately 750 °C, indicating that the structural framework disintegration promoted carbon deposition during the carbon dioxide catalytic process. Figure 11 b). The gaseous species generated during the carbon dioxide catalytic process were detected using optical emission spectroscopy (OES). Figure 11 c). The reactor packed with CeHfZr-UiO-66 produced less gaseous hydroxyl radicals (·OH) and gaseous CO, indicating that the catalyst surface effectively adsorbed more water and CO, providing conditions for the subsequent CC coupling reaction of ethylene.

[0039] The utilization efficiency of high-energy electrons in the NTP system directly determines the carbon dioxide catalytic products generated on the catalyst surface. Electrochemical impedance spectroscopy (EIS) shows that CeHfZr-UiO-66 exhibits a lower charge transfer resistance (Rct), indicating that its excellent conductivity promotes charge transport to the active sites. Figure 11 d). Furthermore, compared to Ce-UiO-66 (5.47 eV), CeHfZr-UiO-66 has a lower work function (4.66 eV), indicating that electrons are more readily emitted to the surface and participate in the adsorption and activation processes of key intermediates. Figure 11 e). In the presence of water, the maximum discharge current in the plasma waveform is attributed to the cancellation of the built-in electric field generated by the wall charge and the applied electric field. During plasma discharge, the accumulation of wall charge is significantly reduced ( Figure 11 f). Simultaneously, the discharge mode shifted from typical linear discharge to surface discharge, indicating a change in the reaction mechanism from gas-phase catalysis to surface-mediated catalysis. The hydrogen-bonded network microenvironment on the CeHfZr-UiO-66 surface serves as a hydrogen source for adjacent unsaturated Lewis acid sites, under which water activation is crucial for ethylene synthesis. (e.g.) Figure 11 As shown in g, the water adsorbed on the CeHfZr-UiO-66 surface can be easily ionized by surface-bound high-energy electrons. Due to proton transfer within the hydrogen bond network, the large number of ·H radicals generated by rapid hydrolysis combine with electrons escaping from the surface to form *H, which subsequently participates in the ethylene synthesis process ( Figure 11 Furthermore, the decrease in hydroxyl (-OH) content in the used CeHfZr-UiO-66 material indicates that the generated ·OH radicals have been consumed through the removal of carbon deposits. Figure 11 i).

[0040] The reaction pathway for the synthesis of ethylene on CeHfZr-UiO-66 in the NTP system is as follows: Figure 12 As shown, firstly, water is adsorbed on the surface of the catalytic material, forming an interconnected hydrogen-bonded network microenvironment. Subsequently, plasma discharge in surface mode ionizes the water within this network, generating ·H radicals and ·OH radicals in situ. ·H radicals are transferred to the active sites via proton transfer within the hydrogen-bonded network and converted into *H, which participates in ethylene synthesis; while ·OH radicals are consumed by surface carbon deposits.

[0041] Furthermore, as shown in Table 3, this invention uses thiol-functionalized Ce-UiO-66 to coat and modify CeHfZr-UiO-66, resulting in a cerium-based metal-organic framework composite catalytic material CeHfZr-UiO-66 / Ce-SH with a more stable structure and more active sites, which further improves the conversion rate of CO2 and the yield of C2H4.

[0042] Table 3 In summary, this invention constructs a hydrogen-bonded network microenvironment on the catalyst surface to achieve non-thermal plasma (NTP)-driven carbon dioxide to ethylene conversion. The synthesized CeHfZr-UiO-66 adsorbs H2O and forms a surface hydrogen-bonded network, thereby optimizing the plasma discharge mode. In a simulated atmosphere containing approximately 20% carbon dioxide and H2O, CeHfZr-UiO-66 achieved an ethylene yield of 164.6 μmol / (g·h), nearly 15 times higher than Ce-UiO-66. Experimental verification and in-situ spectroscopic analysis show that H2O undergoes in-situ ionization on the CeHfZr-UiO-66 surface, generating solvated hydrogen radicals (·H) and hydroxyl radicals (·OH). Oxidizing ·OH radicals are consumed by removing surface carbon deposits; while ·H radicals rapidly migrate to active sites via proton transfer in the hydrogen-bonded network and are converted into adsorbed *H species, participating in the CC coupling reaction to promote ethylene synthesis. After coating modification of CeHfZr-UiO-66, an ethylene yield of 298.3 μmol / (g·h) was achieved by CeHfZr-UiO-66 / Ce-SH in a simulated atmosphere containing approximately 20% carbon dioxide and H2O. This invention provides a feasible material design strategy for plasma-driven carbon dioxide to ethylene conversion.

[0043] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and illustrations shown and described herein.

Claims

1. A method for preparing a cerium-based metal-organic framework composite catalytic material, characterized in that, Includes the following steps: Step 1: Mix terephthalic acid, hydrochloric acid and N,N-dimethylformamide evenly, add metal chloride and stir to obtain a mixed solution; Step 2: Transfer the mixed solution to a reaction vessel, heat the reaction, collect the precipitate and wash it, then vacuum dry it to obtain the cerium-based metal-organic framework composite catalytic material.

2. The preparation method of a cerium-based metal-organic framework composite catalytic material as described in claim 1, characterized in that, In step one, the molar volume ratio of terephthalic acid, hydrochloric acid, and N,N-dimethylformamide is 3~5 mmol:0.2~0.6 mL:10~20 mL; the concentration of hydrochloric acid is 36~38 wt%.

3. The preparation method of a cerium-based metal-organic framework composite catalytic material as described in claim 1, characterized in that, In step one, the metal chloride includes one or more of cerium chloride, hafnium chloride, and zirconium chloride.

4. The preparation method of a cerium-based metal-organic framework composite catalytic material as described in claim 1, characterized in that, In step one, the metal chloride is a combination of cerium chloride, hafnium chloride, and zirconium chloride.

5. The preparation method of a cerium-based metal-organic framework composite catalytic material as described in claim 4, characterized in that, The molar ratio of cerium chloride, hafnium chloride, and zirconium chloride is 1~2:1~2:1~2.

6. The preparation method of a cerium-based metal-organic framework composite catalytic material as described in claim 1, characterized in that, In step one, the molar ratio of terephthalic acid to metal chloride is 1:1~3.

7. The preparation method of a cerium-based metal-organic framework composite catalytic material as described in claim 1, characterized in that, In step two, the heating reaction temperature is 110~130℃ and the time is 12~36h.

8. The preparation method of a cerium-based metal-organic framework composite catalytic material as described in claim 1, characterized in that, In step two, the washing process involves sequentially washing with N,N-dimethylformamide and methanol 2 to 5 times.

9. The preparation method of a cerium-based metal-organic framework composite catalytic material as described in claim 1, characterized in that, In step two, the vacuum drying temperature is 50~70℃ and the time is 8~20h.

10. The application of a cerium-based metal-organic framework composite catalytic material prepared by the preparation method according to any one of claims 1-9 in radiation-catalyzed CO2 conversion.